Analisis Tata Letak Fasilitas Perusahaan Terhadap Produktivitas Kerja dengan Prinsip 5S dan ARC: Studi Kasus : CV. Tata Jaya Sablon - Nur Rizky Maulana Putra; Indro Kirono (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
CV. Tata Jaya Sablon is a textile enterprise that manufactures a diverse array of apparel, including t-shirts, shirts, polos, jackets, and other garments. This organization employs several people who sew and execute different stages of the manufacturing process daily. Field observations indicate that the manufacturing process entails a protracted workflow inside a constrained production area. This research seeks to provide an optimal manufacturing facility layout to foster a productive and efficient work environment. This research used the 5S approach (seiri, seiton, seiso, seiketsu, shitsuke) to enhance space efficiency and provide a recommended layout informed by the ARC diagram. The findings of this analysis indicate that the organization's 5S implementation score attained 75%, thereby earning the designation "Quite Good". Nevertheless, seiri and seiton received the lowest scores; so, it is imperative to establish a designated place for unnecessary items and to create a specific space for organizing essential commodities required for the manufacturing process. The ARC findings indicate that the recommended plan has enhanced the efficiency of movement duration or distance by 29.21%.